1976
DOI: 10.1002/cne.901650107
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic studies of cerebellar histogenesis in the bullfrog tadpole during metamorphosis: The external granular layer

Abstract: Spontaneously metamorphosing bullfrog tadpoles and those induced to metamorphose by injections of thyroid stimulating hormone (TSH) were given a single intraperitoneal injection of thymidine-3H (10 muCi/g body weight). The brains were dissected out at various periods 3 hours to 14 days later, and processed for autoradiography. At the 3-hour interval after thymidine-3H injection, ependymal cells were labelled, but not the external granular layer (EGL) cells. Furthermore, in all the metamorphosing tadpoles inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In anurans, these cell groups undergo extensive modifi cation resulting from the change from aquatic to ter restrial habitat and the development of a tetrapod body form [Larsell, 1925[Larsell, , 1967Gona, 1976], Structur ally, a number of anatomical studies have indicated that anurans have one of the least differentiated ves tibulocerebellar regions of any extant tetrapod [see Ariens Kappers et ah, 1936;Kuhlenbeck, 1975, for re views]. Four to five nuclei have been recognized in the dorsal medullary region in frogs and toads [Larsell, 1923[Larsell, , 1934[Larsell, , 1967Gregory, 1974;Opdam et al, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…In anurans, these cell groups undergo extensive modifi cation resulting from the change from aquatic to ter restrial habitat and the development of a tetrapod body form [Larsell, 1925[Larsell, , 1967Gona, 1976], Structur ally, a number of anatomical studies have indicated that anurans have one of the least differentiated ves tibulocerebellar regions of any extant tetrapod [see Ariens Kappers et ah, 1936;Kuhlenbeck, 1975, for re views]. Four to five nuclei have been recognized in the dorsal medullary region in frogs and toads [Larsell, 1923[Larsell, , 1934[Larsell, , 1967Gregory, 1974;Opdam et al, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of maturational changes ap pears to be almost identical to that seen in all other vertebrates studied, with the con spicuous exception that the external gran ular layer (EGL) is entirely nonprolifera tive [Gona, 1976]. It was also found that this sequence of cerebellar maturation can be experimentally induced by treating premetamorphic tadpoles with thyroxine, administered by either intraperitoneal in jection [Gona, 1973] or implantation of thyroxine pellets in the fourth ventricle , Although cerebel lar maturation takes place during meta morphosis, it was later discovered that a small population of mature Purkinje cells with well-developed dendritic trees are present in the cerebellum of the preme tamorphic tadpole [Gona, 1975;Uray and Gona, 1977], It thus became clear that one population of Purkinje cells in bullfrogs undergoes maturation well before the ap pearance of the EGL, while the rest of the Purkinje cells undergo maturation at the time of metamorphosis.…”
Section: Introductionmentioning
confidence: 73%
“…1968Decker, 1976] and in the cerebellum [Gona. 1973[Gona. , 1976, Therefore, it is not sur prising to observe T4-induced maturational changes in Purkinje cells.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by the very interesting re sults of the initial studies on the general aspects of frog cerebellar maturation [Gona, 1972[Gona, , 1973[Gona, , 1975[Gona, , 1976[Gona, , 1978, we turned our attention to the details of the developmental aspects of the Purkinje cell. The results of the Golgi studies were re ported recently [Gray andGona, 1978, 1979].…”
Section: Introductionmentioning
confidence: 99%